A new strategy for synthesizing endohedral metallocenophanes - Scholz, Gerald; Gleiter, Rolf; Rominger, Frank (Angewandte Chemie. International edition, 2001)
The template-controlled synthesis of π ligands offers new methods for synthesizing endohedral metallocenophanes. This strategy allows the assembly of previously inaccessible bridged metallocenes, for example, the doubly bridged cobaltocenes 2, prepared from 1, n = 3, 4, 5.
Dedicated to Professor Edgar Heilbronner on the occasion of his 80th birthday
Gesehen am 20.10.2020
Keywords: Festschrift